Sosialisasi Petanque Di SMP N 4 Tambang - leni apriani; Mimi Yulianti; Afis Setiawan; Aryuni Khiran Adisty (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2021)
The purpose of this activity is to introduce the sport of petanque originating from France to the public. This service activity was carried out at SMP N 4 TAMBANG with the material provided ranging from playing techniques, how to calculate points and rules in the petanque game. This socialization activity was carried out in three methods, namely: the lecture method to provide theoretical knowledge about petanque sport, the demonstration method for field practice on the technique of playing petanque, and the discussion method to see feedback that occurred during socialization about petanque sport. From the activities carried out, it is hoped that there will be community enthusiasm for developing this petanque sport because petanque sport does not limit the age in the game and has become one of the sports that will be competed in the provincial level sports week event in Riau Province.